Formação política e a experiência do parlamento jovem na cidade de Araraquara/SP - Lima, Giovanna Isis Castro Alves de [UNESP]; Lahuerta, Milton [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Project “Parlamento Jovem” aims to offer political education to students attending public and private schools in the urban area of Araraquara/SP. The initiative pretends to provide knowledge about democratic institutions and its practices, since the rapprochement between young citizens, politics and its instruments appears as a fundamental path towards the consolidation of democracy. The considerations will be made based on the student’s propositions, formulated during the second phase of the Project, which provides extensive material for analysis and discussion of educational, social and political conditions in the brazilian context.

O Projeto “Parlamento Jovem” tem como propósito oferecer formação política para alunos regularmente matriculados nas escolas das redes estaduais, municipais e particulares do município de Araraquara/SP. A iniciativa pretende proporcionar condições de entendimento sobre as instituições democráticas, bem como suas práticas, uma vez que a aproximação dos jovens cidadãos com a política e seus instrumentos delineia o caminho fundamental em direção à consolidação da democracia. As proposituras redigidas pelos alunos como resultado da segunda etapa do Projeto nos fornecem um amplo material para análise e discussão das condições educacionais, sociais e políticas no contexto brasileiro e é a partir delas que teceremos nossas considerações.
Keywords: Political education; Citizenship; Democracy; Educação política; Cidadania; Democracia